Effects of intranasal oxytocin on neural reward processing in children and adolescents with reactive attachment disorder: A randomized controlled trial - Takiguchi, Shinichiro; Makita, Kai; Fujisawa, Takashi X.; Nishitani, Shota; Tomoda, Akemi (Frontiers in Child and Adolescent Psychiatry, 2023)
Reactive attachment disorder (RAD) is associated with socially and emotionally withdrawn/inhibited behaviors, and reduced neural responses to rewards. Children and adolescents with RAD show aberrant attachment behaviors, and existing psychotherapies are difficult to maintain; therefore, pharmacological interventions to aid and boost treatment responses are needed. Oxytocin (OT) administration is known to promote reward functioning. We investigated whether single-use intranasal OT administration improved neural responses during reward processing in patients with RAD compared with healthy controls. Twenty-four male children and adolescents with RAD (10–18 years old) and 27 age- and sex-matched typically developing individuals (10–17 years old) were included in a randomized, double-blind, placebo-controlled, cross-over, functional magnetic resonance imaging study. Following a single intranasal OT (24 IU) or placebo administration, neural responses were investigated using a monetary reward task. In the RAD group, OT significantly increased subjective motivation scores, significantly enhanced activation in the right middle frontal gyrus, and reduced activation in the right precentral gyrus during the monetary reward task. Additional analyses revealed increased activation in the bilateral caudate at a more lenient threshold. Under placebo conditions, the severity of internalizing problems in patients with RAD was negatively correlated with ventral striatal activity. Moreover, the effect of OT on ventral striatum activity was positively associated with the severity of internalizing problems in patients with RAD. Intranasal OT administration enhanced activity in the reward pathway in male children and adolescents with RAD, suggesting that exogenous OT promotes reward processing and reward-related motivational behavior in these individuals. Further investigation is needed to fully understand the neural mechanisms of intranasal OT and identify novel targets for pediatric cases with RAD Clinical trial registration: UMIN-CTR; UMIN000013215 URL: https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000015419